The Effects of Chilean Coho Salmon and Rainbow Trout Aquaculture on Markets for Alaskan Sockeye Salmon - Williams, Abby; Herrmann, Mark; Criddle, Keith R. (North American Journal of Fisheries Management, 2009)
Abstract A simultaneous‐equation equilibrium model of international salmonid markets is used to examine the combined effect of variability in the landings of Alaska's sockeye salmon Oncorhynchus nerka and increases in the production of Chile's Atlantic salmon Salmo salar , coho salmon O. kisutch , and rainbow trout O. mykiss on Alaska's sockeye salmon exvessel prices and revenues. While Atlantic salmon, coho salmon, and rainbow trout from Chile and sockeye salmon from Alaska are not identical commodities, they compete in many of the same domestic and international markets, and Alaska's earnings in those markets have declined as Chile's production has increased. Although Alaska's average annual harvests have remained nearly constant, Alaska's production is now a small percentage of the total salmonid production in a world that eats significantly more salmonids than it did 25 years ago. Nevertheless, our model indicates that sockeye salmon prices continue to be sensitive to interannual variations in the quantity of sockeye salmon harvested in Alaska and to changes in the quantity of Atlantic salmon, coho salmon, and rainbow trout produced in Chile. However, the model indicates that exvessel revenues are less sensitive than exvessel prices and that Alaska's recent levels of sockeye salmon landings have been near the maximum of the total exvessel revenue curve. In addition, the model suggests that because Alaska's share of the production of high‐value salmon (Chinook, coho, and sockeye salmon) has declined, exvessel prices for sockeye salmon are now less sensitive to changes in Chilean production of Atlantic salmon, coho salmon, and marine‐reared rainbow trout. The implication of these findings is that, under current market conditions, exvessel revenues from Alaska's sockeye salmon fisheries can be maximized by maintaining catches at or near historic levels and that exvessel prices are unlikely to continue to decline as rapidly as they did in the 1990s.